What produces and what controls the spatial-temporal structuring of the magnetospheric chorus waves that create the pulsating aurora: An unsolved problem in need of new measurements - Borovsky, Joseph E.; Partamies, Noora (Frontiers in Astronomy and Space Sciences, 2022)
In this Perspective article discussing solved and unsolved problems in space physics, the focus is on the unsolved problem of the spatial-temporal variability of the magnetospheric plasma waves that produce the spatial-temporal atmospheric luminosity of the pulsating aurora. In particular the outstanding issue of what causes the spatial-temporal variations of the chorus-wave intensities is highlighted: Two great unknowns are (1) how does it work and (2) what are the controlling factors. The point is made that the whistler-mode chorus waves that produce the pulsating aurora are the same chorus waves that energize the Earth’s electron radiation belt. Hence, beyond not understanding the cause of pulsating aurora there is (1) a lack of understanding of the magnetosphere-ionosphere system behavior and (2) a lack of understanding of how the electron radiation belt is energized. It is noted that the pulsating aurora is perhaps the most-obvious example of an “emergent phenomena” in the magnetosphere-ionosphere-thermosphere system, and so perhaps the clearest indication that the magnetosphere-ionosphere-thermosphere system is a truly “complex system”, not just a complicated system. Future needs for solving this unsolved problem are discussed: the most-critical need is argued to be gaining an ability to measure cold-electron structuring in the equatorial magnetosphere.